Effect of moderate intensity continuous exercise on the life quality and physiological status of college Obese students - Cabauatan, King Abram F. (Edelweiss Applied Science and Technology, 2025)
This study investigated the effects of Moderate Intensity Continuous Exercise (MICE) on the quality of life and physiological status of obese college students. Employing a Solomon Four-Group experimental design, the research involved 60 obese students from a state university in Negros Occidental. The Quality of Life Scale (QOLS) by John Flanagan measured life quality, while the Philippine Physical Fitness Test assessed physiological status. Descriptive statistics (mean, standard deviation) and inferential tests (independent and dependent t-tests at a 0.05 significance level) were used to analyze the data. Findings revealed that both the MICE (experimental) and Zumba (control) groups improved in life quality from “mostly satisfied” to “delighted” post-intervention. Physiological status, initially “above average” for both groups, improved to “good” in the MICE group but remained “above average” in the Zumba group. Although there were no significant differences in pretest or posttest scores between the groups, both interventions led to statistically significant improvements over time. The results suggest that MICE is comparably effective to Zumba in enhancing life quality and may offer superior benefits for physiological status. These findings support the integration of MICE into wellness programs for obese students as a viable and effective physical activity intervention.